Study Protocol: Does an Acute Intervention of High-Intensity Physical Exercise Followed by a Brain Training Video Game Have Immediate Effects on Brain Activity of Older People During Stroop Task in fMRI?—A Randomized Controlled Trial With Crossover Design - Himmelmeier, Robin Maximilian; Nouchi, Rui; Saito, Toshiki; Burin, Dalila; Wiltfang, Jens; Kawashima, Ryuta (Frontiers in Aging Neuroscience, 2019)
Background Elderly people are affected by processes leading to decline in various aspects of daily living that impair their quality of life. Regarding neurological aspects, executive functions have been shown to be valuable for daily life and to slow decline during aging. Most intervention studies intended to improve cognitive functions during aging specifically address long-term destructive processes and countermeasures. However, to an increasing degree, studies also investigate the acute benefits that prove to be useful for daily life, such as physical exercise or video games in the form of exercise video gaming (“exergaming”). Because little is known about the change in cognitive ability following acute intervention of a combination of physical exercise and video gaming, especially for older people, this work is designed as an attempt to address this matter. Methods This study is a randomized crossover controlled trial to test the response to an acute bout of high-intensity physical exercise followed by a short session with a brain training (Brain Age) video game in physically active and cognitively healthy older adults (60–70 years). The response is measured using Stroop task performance (cognitive task for executive function) and related brain activity assessed with functional magnetic resonance imaging (fMRI). The control conditions are low-intensity physical exercise and Tetris for video gaming. Discussion This study is intended to provide insight into the alteration of executive function and its related brain activity from an acute intervention with a combination of physical exercise and video gaming in older people. The protocol might not be implementable in daily life to improve cognitive abilities. However, the results can support future studies that investigate cognition and the combination of physical exercise and video gaming. Moreover, it can provide real-life implications. Trial registration This trial was registered in The University Hospital Medical Information Network Clinical Trials Registry (UMIN000033054). Registered 19 July 2018, https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000037687